Violation of Article 2. and Article 9. of European Convention of Human Rights by Russian Federation in the occupied territory of Crimea - Danga, Suzanna (Riga Graduate School of Law, 2021)
Thesis analyses Article 2 and Article 9 ECHR concerning violations in the annexed territory of Crimea. Russia’s annexation of Crimea and its military presence in the Eastern Ukraine region is still topical issue in the world, because conflict have not been solved. Since the annexation life and human right situation in Crimea have been hidden. Right of life and freedom of religion are fundamental rights of people, therefore Russia as member state of the Council of Europe is obliged to protect these rights. Regarding violations of articles 2 and 9 in Crimea, case law of the European Court of Human Rights was used for the analysis, which proved that Russia has violated human rights. As well as norms and principles of international law to evaluate process of annexation. Right of self-determination and impact of religion was also researched and concluded, that Crimea did not possessed right of self-determination.
Keywords: Human rights; Crimea; Russian Federation